2012
DOI: 10.1302/0301-620x.94b6.28373
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of pseudotumour formation after large-diameter metal-on-metal total hip replacement

Abstract: Peri-articular soft-tissue masses or 'pseudotumours' can occur after large-diameter metal-on-metal (MoM) resurfacing of the hip and conventional total hip replacement (THR). Our aim was to assess the incidence of pseudotumour formation and to identify risk factors for their formation in a prospective cohort study. A total of 119 patients who underwent 120 MoM THRs with large-diameter femoral heads between January 2005 and November 2007 were included in the study. Outcome scores, serum metal ion levels, radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 28 publications
(25 reference statements)
5
170
3
8
Order By: Relevance
“…Extensive soft tissue damage is more commonly encountered in MoM hips revised for aseptic loosening than hips with other bearing surfaces with severe bone loss reported as well [1,8]. The extent of adverse local tissue response confronted at the time of revision poses genuine concern for outcome as it pertains to fixation, stability, and, potentially, infection [7,10,13,39].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive soft tissue damage is more commonly encountered in MoM hips revised for aseptic loosening than hips with other bearing surfaces with severe bone loss reported as well [1,8]. The extent of adverse local tissue response confronted at the time of revision poses genuine concern for outcome as it pertains to fixation, stability, and, potentially, infection [7,10,13,39].…”
Section: Resultsmentioning
confidence: 99%
“…Of the available articles, 10 discussed HRA outcomes, whereas three outlined MoM THA outcomes. Given the paucity of data evaluating MoM THA [3,25,28], the systematic review was narrowed to only include HRA studies. At the outset of the systematic review, the author's hope was that pooled data evaluating clinical outcomes scores could be reviewed.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Bayley et al [2] found no correlation between the presence of pseudotumor and any of the risk factors they examined including elevated metal ion levels, femoral head size and head-neck taper length, among others. This was an unexpected result since previous studies had reported an increased risk of pseudotumor development with increased metal ion levels [5,16], which may indicate that patientspecific factors such as metal hypersensitivity may be more involved in pseudotumor formation than previously believed [2]. Based on conflicting results, more research may be necessary to examine the relationship between pseudotumor development and metal ion levels.…”
Section: Discussionmentioning
confidence: 78%
“…The use of metal-on-metal (MoM) bearings is no longer prevalent due to frequent reports of periarticular soft tissue masses, or pseudotumors [5,12,16,21]; elevated local and systemic metal ion levels [3,18,24,29]; and early failure rates seen in some implant designs [17,27]. Although there has been a resurgence of the use of these bearings in the last 20 years, their use in stemmed total hip arthroplasty is not currently recommended based on the negative outcomes that have been reported in the literature [1,4,20,27].…”
Section: Introductionmentioning
confidence: 99%